Possibilidades e limites da responsabilidade tributária do grupo econômico no ordenamento jurídico brasileiro - Lima, Diana de Melo Costa (2023)
The central question in this study is to investigate, in the light of the Brazilian legal system, whether the aggregation of legal entities in a de facto regular economic group implies joint and several liability for the tax debts generated by it. This is an issue that generates controversy given the conceptual difficulty and lack of uniformity in the legislation to establish the minimum parameters for applying the sanctions provided for in the legislation, hence the relevance of this study, as it brings a more delimited proposal about the tax liability of economic groups. Thus, the following question arises: what are the possibilities and limits of tax liability within the Brazilian legal system within the scope of the economic group? It is noticed that the Brazilian legal system does not support indiscriminate tax liability of the legal entities that are part of the group, being necessary, at least, a contribution or a certain connection in the practice of acts contrary to the law that lead to the birth of the tax or its evasion, or even the practice of licit acts referred to the tax legal fact. Taking this problem into account, the general objective is: to analyze the tax liability of legal entities that are part of an economic group, in order to reach the possibilities and limits within the Brazilian legal system. The study is based, above all, on the reference system of Logical-Semantic Constructivism, headed in Brazil, mainly by Vilanova (2005) and Carvalho (2005, 2016, 2018, 2021). The study of passive tax subjection was undertaken, focusing on the responsibility of people who did not practice the legal tax act, turning to the constitutional and legal limits to the power to tax, as well as to the conceptual bases involving this object of study. The study is characterized by a qualitative approach, using exploratory research methods and bibliographical and jurisprudential data collection techniques. The study reveals that the mere grouping of companies is not legally relevant for attributing tax liability among them for tax debts generated by one and not necessarily by other companies belonging to the same group. Currently, the Brazilian legal system only allows joint and several liability to be attributed between companies of a de facto irregular economic group. Regarding companies that are part of a regular economic group, it is only possible to attribute responsibility to the company that, licitly or illicitly, has contributed to the legal fact of the tax obligation.